Flexible organic tandem solar modules with 6% efficiency: combining roll-to-roll compatible processing with high geometric fill factors - Spyropoulos, Georgios; Kubis, Peter; Li, Ning; Baran, Derya; Lucera, Luca; Salvador, Michael Filipe; Ameri, Tayebeh; Voigt, Monika; Krebs, F. C.; Brabec, Christoph (Energy and Environmental Science, 2014)
Organic solar cell technology bears the potential for high photovoltaic performance combined with truly low-cost, high-volume processing. Here we demonstrate organic tandem solar modules on flexible substrates fabricated by fully roll-to-roll compatible processing at temperatures <70 °C. By using ultrafast laser patterning we considerably reduced the “dead area” of the modules and achieved geometric fill factors beyond 90%. The modules revealed very low interconnection-resistance compared to the single tandem cells and exhibited a power conversion efficiency of up to 5.7%. Bending tests performed on the modules suggest high mechanical resilience for this type of device. Our findings inform concrete steps towards high efficiency photovoltaic applications on curved, foldable and moving surfaces.
Keywords: Fill factor; Roll to Roll; Solar module GEOBASE Subject Index: photovoltaic system; resilience; solar power; volume

High performance ternary organic solar cells with thick active layer exceeding 11% efficiency - Gasparini, Nicola; Lucera, Luca; Salvador, Michael Filipe; Prosa, Mario; Spyropoulos, Georgios; Kubis, Peter; Egelhaaf, Hans Joachim; Brabec, Christoph; Ameri, Tayebeh (Energy and Environmental Science, 2017)
We present a novel ternary organic solar cell with uncommonly thick active layer (>300 nm), featuring thickness invariant charge carrier recomb ination and delivering 11% power conversion efficiency (PCE). The ternary blend was used to demonstrate photovoltaic modules of high technological relevance both on gla ss and flexible substrates, yielding 8.2% and 6.8% PCE, respectively.

High precision processing of flexible P3HT/PCBM modules with geometric fill factor over 95% - Kubis, Peter; Lucera, Luca; Machui, Florian; Spyropoulos, Georgios; Cordero, Johann; Frey, Alfred; Kaschta, Joachim; Voigt, Monika; Matt, Gebhard; Zeira, Eitan; Brabec, Christoph (Organic Electronics, 2014)
Flexible OPV modules, based on P3HT:PCBM as absorber layer, were manufactured with a power conversion efficiency over 3% and for a total area of 3500 mm(2) consisting of 14 in series interconnected cells. The modules utilize the excellent mechanical and the outstanding optical properties of sputtered transparent ITO-Metal-ITO (IMI) electrodes deposited on the PET foil on the one hand, and the combination of large area slot-die coating with high resolution ultrafast laser patterning on the other hand. The manufacturing of modules with outstanding performance was found to be reproducible. The right combination of innovative electrodes and smart roll-to-roll compatible processing technologies demonstrates a viable path towards high efficient industrial module technology. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Flexible transparent electrode; Flexible OPV module; Slot-die coating; Ultra-fast laser patterning; High geometric fill factor